The Impact of Economics Education on The Frugal Lifestyle Attitude of 12th-Grade Students - Anggi Septia Nugroho; Ulil Albab (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Students' frugal attitude is influenced in part by their understanding of economics education delivered by teachers. Economics education is a dynamic learning process closely linked to students' everyday lives, encompassing concepts like needs, priority scales, and economic principles. This research aims to investigate the impact of economics education on students' frugal lifestyles. It employs a qualitative descriptive approach, specifically a case study research design. The findings reveal that 1) The economics education process at MAN 1 Terbanggi Besar consists of several stages: (a) The pre-instructional stage, an initial phase where the teacher takes attendance, inquires about previous discussions, conducts post-tests and pre-tests, and briefly reviews prior material. (b) The instructional stage, involving the presentation of prepared lesson materials, which includes explaining learning objectives, delivering subject matter, providing concrete examples, using tools and media, and summarizing discussion outcomes. (c) The evaluation stage, aimed at assessing the success level of the second stage, the instructional phase. 2) The Impact of Economics Education on the Frugal Lifestyle Attitude of 12th-Grade Students at MAN 1 Terbanggi Besar encompasses: (a) Prioritizing needs over wants, (b) Being wise in spending, (c) Leading a simple life, (d) Practicing disciplined saving.